2017
DOI: 10.1002/crq.21206
|View full text |Cite
|
Sign up to set email alerts
|

Italian Mediators in Action: The Impact of Style and Attitude

Abstract: Abstract:We analyzed a questionnaire sent to Italian mediators. We sought to investigate three areas: style of mediation; personal attitude towards the conflict; effectiveness in leading the parties to a negotiated agreement in mediation. We found no significant correlations between the style of mediation and the attitude of the respondents to the conflict. Respondents with a post-graduate training in economics or accounting achieved higher rates of settlement. The style of the mediator may be of some use as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(39 reference statements)
1
2
0
1
Order By: Relevance
“…Our finding of both types of negotiators in Italy aligns with the picture presented by Cominelli and Lucchiari (2017) and Caputo and Valenza (2019), who identify a continuum that ranges from 'Competing' (a conflict management style that implies a win-lose perspective) to 'Collaborating' (a view of conflicts as problems to be solved jointly, which means searching for a win-win solution). This divide in the Italian results on negotiation styles could mirror Italy's strong cultural differentiation between North and South (Clò, 2006) a possibility that could be further examined by comparing data that include negotiators' regional provenance (Kaasa, Vadi, & Varblane, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Our finding of both types of negotiators in Italy aligns with the picture presented by Cominelli and Lucchiari (2017) and Caputo and Valenza (2019), who identify a continuum that ranges from 'Competing' (a conflict management style that implies a win-lose perspective) to 'Collaborating' (a view of conflicts as problems to be solved jointly, which means searching for a win-win solution). This divide in the Italian results on negotiation styles could mirror Italy's strong cultural differentiation between North and South (Clò, 2006) a possibility that could be further examined by comparing data that include negotiators' regional provenance (Kaasa, Vadi, & Varblane, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Research studies have found that mediator‐related variables—including but not limited to gender, professional background, work experience in mediation, mediation orientation, personal attitude toward conflict, and skills in leading mediation—highly influence service outcomes such as settlement rate, durability of agreement, user's willingness to recommend mediation, and user's rating of mediator performance (Cominelli & Lucchiari, ; Folberg & Taylor, ; Gale, Mowery, Herrman, & Hollett, ; Goldberg & Shaw, ). These studies make significant contributions to our understanding of mediation and indicate that it is worth further investigating the effect of mediator‐related factors, such as the mediator's professional competence and mediation process, on service outcomes in different cultural and social contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed entropy-based methodology is global and applicable to handling the conflict of heterogeneous groups and where there can be people with various knowledge bases, educational backgrounds, experiences, gender, and professions. Apart from the present case, the approach applies to the following existing case studies and literature without any change in methodology: conflict on e-learning (Zervos et al, 2013), conflict about legislative initiatives at the international level and the European level (Cominelli & Lucchiari, 2017), conflict of interest among Italian medical oncologists (DeCensi et al, 2018), a Portuguese case study of tourism conflict (Almeida et al, 2018) and many more. Due to space limitations, we have not described the results of each case study.…”
Section: Anjariamentioning
confidence: 99%